Organic fish farming: a pioneer approach towards sustainable fish farming - Kaur, Rajinder; Shah, Tarang Kumar (Indian Farming, 2018)
Organic fish farming is a new concept and is still in the early stages of development and strives to reestablish a proper balance in aquaculture systems, for the benefit of fisheries, environment and the consumers. Organic fish farming systems and standards that define them are likely to witness considerable evolution andrefinement over the years. Nutrient cycling within closed systems,following the law of return, is a central organic principle. By exploring the strength and opportunities mentioned in the SWOT analysis and solving the threats and weaknesses would pave way for organic aquaculture to be a new revolution towards the sustainable fisheries in India and rest of the world. Many organic aquaculture issues still need to be resolved. Steps should be taken to encourage and enhance the biological cycles with respect to nutrients management and to retain the integrity of the organic product from farmer to consumer and conversion requirement for moving conventional aquaculture system into organic system.